Meningkatkan Standar Proses melalui Pelaksanaan Supervsisi Akademik pada Jenjang Sekolah Dasar di Kecamatan Gantarang Kabupaten Bulukumba - Muhabbabe Muhabbabe; Effendi M (MANAZHIM, 2021)
Objective conditions that occur in schools, where teachers in carrying out teaching tasks without good planning certainly cannot create conducive learning conditions for improving the quality of student learning processes and outcomes. To improve such conditions, it can be done by carrying out teacher development through the implementation of academic supervision in the hope that teachers have the will to continuously improve their competency feasibility. The problems studied are (1) how is the model for fostering junior teachers in order to make a learning implementation plan oriented to active student learning, (2) how is the coaching model for junior teachers in order to implement a learning implementation plan oriented to active student learning, (3) whether the development of junior teachers through the implementation of academic supervision can improve the ability of teachers to make lesson plans oriented to active learning models, and (4) whether the development of junior teachers through the implementation of academic supervision can improve the ability of teachers to implement lesson plans that well made. The results of the data analysis show that: (1) the development of junior teachers carried out through the implementation of academic supervision can improve the ability of teachers to make learning implementation plans oriented to the active learning model, and (2) the development of junior teachers through the implementation of academic supervision. improve the ability of teachers to carry out learning based on a well-made lesson plan.